Pengaruh Pengetahuan Perpajakan, Sosialisasi Pajak, dan Tax Morale Terhadap Niat Untuk Patuh Calon Wajib Pajak - Katarina Aprila Sumule; Teguh Erawati (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to determine the effect of tax knowledge, tax socialization, and tax morale on the intention to comply with prospective taxpayers. This study uses primary data through a questionnaire. The sample in this research is active students of the Accounting Study Program batch 2019 to 2021 at the Tamansiswa University of Yogyakarta. The sample technique used is Convenience Sampling. The number of samples in this study were 100 respondents. The results showed that knowledge of taxation had a positive effect on the intention to comply with prospective taxpayers, tax socialization had no effect on the intention to comply with prospective taxpayers, and tax morale had a positive effect on the intention to comply with prospective taxpayers.